Performance Analysis of Time Capacity and Coulomb Methods for SoC Estimation in VRLA Batteries - Herlina; M. Rafli Leo; Sri Agustina; Wirawan Adi Pradana (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2025)
The climate crisis and limited energy availability in remote areas encourage the use of VRLA battery-based off-grid solar energy systems, where accurate state-of-charge (SoC) evaluation is essential for system efficiency. At middle SoC ranges, the VRLA voltage curve's flatness makes voltage-based methods less effective. This research investigates the efficacy of two practical methods, Time Capacity and Coulomb Counting, in estimating the SoC of 12V 10Ah VRLA batteries at varying discharge rates (C20 to C1) using a system that incorporates Arduino Uno and ACS712 sensors. The experimental findings show that Time Capacity is the best strategy, with an inaccuracy of 0-12%. Due to sensor error and temperature sensitivity, Coulomb Counting's error is 30-38.4%. Heatmap imaging proved Time Capacity's stability across all C-rates, making it suitable for remote monitoring. These findings lay the groundwork for reliable and cost-effective renewable energy systems and encourage further research on hybrid algorithms and environmental optimisation.